Increased Risk of Extreme Precipitation Over an Urban Agglomeration With Future Global Warming. Issue 6 (23rd June 2022) - Doan, Quang‐Van; Chen, Fei; Kusaka, Hiroyuki; Dipankar, Anurag; Khan, Ansar; Hamdi, Rafiq; Roth, Matthias; Niyogi, Dev
Abstract: Understanding the response of extreme precipitation (EP) at a city scale to global warming is critical to reducing the respective risk of urban flooding. Yet, current knowledge on this issue is limited. Here, focusing on an urban agglomeration in the tropics, Singapore, we reveal that future global warming enhances both frequency and intensity of EP, based on simulations with a state‐of‐the‐art convection‐permitting regional climate model. EP intensification can reach maximum "super" Clausius‐Clapeyron rate ( ≥ $\ge $ +7% per K warming) rate, implying a "new normal" of "extreme events get more extreme, " which is consistently for both Representative Concentration Pathways 8.5 and 4.5. The intensification is lower for moderate and light precipitation. Also, global warming was found to dampen the urban effect on EP events. The EP enhancement is attributed to the increased atmospheric moisture and convective inhibition due to enhanced low‐level stratification that delays a convection to develop until it becomes more intense. Plain Language Summary: Understanding the response of extreme precipitation (EP) at a city scale to global warming is critical to reducing the respective risk of urban flooding. Here we show that future global warming will enhance both frequency and intensity of EP, based on simulations with a state‐of‐the‐art convection‐permitting regional climate model for an urban agglomeration in the tropics, Singapore. EP is estimated to intensify much more than moderate and light precipitation, implying a "new normal" of "the extreme events get more extreme." Also, global warming was found to dampen the urban effect on EP events. The EP enhancement is attributed to the increased atmospheric moisture and convective inhibition due to enhanced low‐level stratification that delays a convection to develop until it becomes more intense. Key Points: New normal of "extreme events get more extreme" in future city‐scale precipitation is revealed Global warming could modify and even reduce the urban footprint on extreme precipitation (EP) events The intensification of EP can reach the maximum at the "super" Clausius‐Clapeyron ( ≥ $\ge $ +7% per K warming) rate